Knowledge Regarding Child Victims of Commercial Sexual Exploitation and the Feasibility of Using a Smartphone Application: A Pilot Study. Issue 2 (April 2019) - Goldman, Sheree; Goyal, Deepika
ABSTRACT: Purpose: This pilot study examined the knowledge level and feasibility of using a smartphone application (app) to identify victims of sexual exploitation. Methods: Using a quantitative, pretest–posttest design, a convenience sample of 103 law enforcement officers living in the Western United States was assigned to a control ( n = 38) or intervention ( n = 65) group. Participants provided demographic data and completed an investigator-developed questionnaire to assess their knowledge of commercial sexual exploitation of children (CSEC). Questionnaires were completed twice, with the intervention group completing the posttest after being given the opportunity to test-drive a smartphone app designed to identify CSEC victims. Participants in the intervention group were also asked to rate the ease and usefulness of the app and preferred format of resources. Data were analyzed using descriptive statistics and mixed analysis of variance. Results: Few participants had received training in CSEC. Knowledge increased significantly more for the intervention group compared with the control group ( p = 0.009), and similar results were noted with CSEC protocol questions ( p = 0.005). Intervention group participants stated the app was easy to use (59%) and useful (63.9%) and preferred the CSEC information in the form of an app versus printed materials (85%). Conclusion: Results of this study suggest an overall low level of CSEC knowledge in our sample of law enforcement officers. However, a smartphone app may be feasible in identifying victims of sexual exploitation. Earlier recognition of CSEC victims promotes earlier referral to interdisciplinary health and human services.